2022
DOI: 10.3390/buildings12101496
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Strengthening Method for Preventing Collapsed of Vulnerable Masonry Infills

Abstract: A series of structural tests were conducted to examine the seismic performance of masonry infills strengthened with particular materials on infilled reinforced concrete (RC) frame structures. Six 1:4 scaled-down RC frame specimens had been prepared, including one brick-infilled frame without strengthening and five brick infills strengthened with innovative strengthening materials. The materials were steel wire mesh, chicken hexagonal wire mesh, plastic wire mesh, fiber-reinforced polymer (FRP), and plastic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Meanwhile, the analysis of masonry buildings has been widely investigated where previous studies have shown that earthquake loads affect the seismic response of masonry build-ings. This is due to several factors such as the quality of the bricks used, the relation-ship between the masonry, the durability of the bricks, the irregularity of the structure, and the characteristics of the ground motion [1]. Maidiawati et al * Corresponding Author : masrilayanti@eng.unand.ac.id states in theirs research that he experimental results showed that most specimens exhibited an increase in their lateral strength, secant stiffness, deformatio capacity, and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the analysis of masonry buildings has been widely investigated where previous studies have shown that earthquake loads affect the seismic response of masonry build-ings. This is due to several factors such as the quality of the bricks used, the relation-ship between the masonry, the durability of the bricks, the irregularity of the structure, and the characteristics of the ground motion [1]. Maidiawati et al * Corresponding Author : masrilayanti@eng.unand.ac.id states in theirs research that he experimental results showed that most specimens exhibited an increase in their lateral strength, secant stiffness, deformatio capacity, and energy dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…The plates are sliding northeastward at about 7 cm per year and dipping under the Sunda plate, which encompasses Sumatra and Singapore [2,3]. The city is one of the disaster-prone areas in Indonesia due to its territory lies within one of the world's most active fault lines namely the "Ring of Fire" [1]. One of the major earthquakes that affected Padang includes the Mw 7.6 earthquake which occurred off the island of Sumatera, near the city of Padang on 30 September 2009.…”
Section: Introductionmentioning
confidence: 99%